Sediment accretion and nutrient enrichment enhance the growth and vegetative propagation of Phalaris arundinacea growing within a Carex thunbergii stand - Guo, Xin-zhi; Zhong, Jia-shun; Sun, Wen-jing; Song, Xiang-rong; Liu, Jing; Chen, Xin-sheng (Frontiers in Plant Science, 2024)
Sediment accretion (burial) and nutrient enrichment may exert a synergistic influence on the growth and distribution of macrophytes in floodplain wetlands; however, this phenomenon has rarely been examined. In this study, we investigated the effects of sediment accretion and nutrient enrichment on the growth and vegetative propagation of Phalaris arundinacea within a Carex thunbergii stand (one P. arundinacea ramet within 25 C. thunbergii ramets) using a factorial sediment burial (0, 3, and 6 cm) and nutrient addition (low, medium, and high) experimental design. High sediment burial (6 cm) without nutrient addition decreased the aboveground and total biomass of C. thunbergii but did not affect P. arundinacea, indicating that P. arundinacea is more tolerant to sediment burial than C. thunbergii. Moderate sediment burial (3 cm) with nutrient addition enhanced the aboveground and total biomass of P. arundinacea but did not affect C. thunbergii, indicating that P. arundinacea may gain a growth advantage over C. thunbergii under moderate sedimentation. High sediment burial with nutrient addition increased the number of rhizomes and ramets produced by P. arundinacea but did not affect C. thunbergii, indicating that the relative abundance of P. arundinacea may increase within the Carex community under high sedimentation conditions. Based on these results, it can be concluded that an increased sedimentation rate facilitates the invasion of P. arundinacea into Carex grasslands, and this invasion is further enhanced by nutrient enrichment. Therefore, management measures should be taken to reduce the sediment load and nutrient input to prevent Carex grasslands invasion by P. arundinacea and maintain the ecological function of floodplain wetlands.